Measurement of plasma electron temperature and density by using different applied voltages and working pressures in a magnetron sputtering system - N. Mazhir, Sabah; K. Khalaf, Mohammed; K. Taha, Sarah; K . Mohsin, Hussein (International Journal of Engineering and Technology, 2018)
This paper discusses applying different voltages and pressure in the presence of silver target and argon gas to produce plasma. Home-made dc magnetron sputtering system was used to produce glow discharge plasma. The distance between two electrodes is 4 cm. Gas used to produce plasma is argon that flows inside the chamber with flow rate 40 sccm. Intensity of spectral lines, electron temperature and electron density were studied. The results show that the intensity of spectral lines increases with the increase of the working pressure and applied voltage. Electron temperature increases by the increase of applied voltage but decreases with the increase of working pressure, while electron density decreases with the increase of applied voltage and increases with the increase of working pressure. This research demonstrates a new low cost approach to start producing high corrosion resistance materials.Â Â